Insights on the concept of indicator populations derived from parentage‐based tagging in a large‐scale coho salmon application in British Columbia, Canada. Issue 13 (18th May 2020) - Beacham, Terry D.; Wallace, Colin; Jonsen, Kim; McIntosh, Brenda; Candy, John R.; Willis, David; Lynch, Cheryl; Withler, Ruth E.
Abstract: For Pacific salmon, the key fisheries management goal in British Columbia (BC) is to maintain and restore healthy and diverse Pacific salmon populations, making conservation of salmon biodiversity the highest priority for resource management decision‐making. Salmon status assessments are often conducted on coded‐wire‐tagged subsets of indicator populations based on assumptions of little differentiation within or among proximal populations. In the current study of southern BC coho salmon ( Oncorhynchus kisutch ) populations, parentage‐based tagging (PBT) analysis provided novel information on migration and life‐history patterns to test the assumptions of biological homogeneity over limited (generally < 100 km) geographic distances and, potentially, to inform management of fisheries and hatchery broodstocks. Heterogeneity for location and timing of fishery captures, family productivity, and exploitation rate was observed over small geographic scales, within regions that are, or might be expected to be, within the area encompassed by a single‐tagged indicator population. These results provide little support for the suggestion that information gained from tagged indicator populations is representative of marine distribution, productivity, and exploitation patterns of proximal populations. Abstract : Salmon status assessments are often conducted on coded‐wire‐tagged subsets of indicator populations based on the assumptions of little differentiation within or among proximal populations. In the current study of southern BC coho salmon ( Oncorhynchus kisutch ) populations, parentage‐based tagging (PBT) analysis provided novel information on migration and life‐history patterns to test the assumptions of biological homogeneity over small geographic distances and, potentially, to inform management of fisheries and hatchery broodstocks.